PERAN ALGORITMA TIKTOK DALAM PEMBENTUKAN PREFERENSI DAKWAH GENERASI Z: ANALISIS KONTEN AKUN @KADAMSIDIK00 - Artika Lestari, Desti; Lutfiyah, Aini; Huda, Shohibul; Suryandari, Meity (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of the TikTok algorithm in shaping Generation Z’s da’wah preferences through content analysis of the @kadamsidik00 account. The development of algorithm-based social media has transformed information distribution, including Islamic preaching practices in digital spaces. This research employs a qualitative approach using content analysis of 20 selected videos based on the highest engagement levels during January–March 2025. The findings indicate that the TikTok algorithm prioritizes the distribution of content characterized by brevity, visual appeal, and communicative delivery, which aligns with Generation Z’s preferences. Content presented in a casual and relatable manner tends to generate higher engagement, increasing its likelihood of being recommended by the algorithm. These results suggest that the algorithm functions not only as a distribution mechanism but also as a factor shaping audience consumption patterns and da’wah preferences. This study contributes to the development of digital Islamic communication studies by positioning algorithms as key actors in shaping da’wah preferences and providing insights into the implications of social media use in contemporary Islamic preaching.